Importance of parasitic foodborne diseases in rural areas of southern Laos: A long-term case study using an integrated approach - Putthana, V.; Promburom, P.; Lacksivy, T.; Meunsen, D.; Keosengthong, A.; Danner, G.; Keonam, K.; Changleuxai, P.; Adsanychanh, N.; Sanamxay, D.; Suthammavong, P.; Ninnasopha, K.; et al. (2016)
Parasites foodborne diseases (PFBD) are expected to be widely distributed in Laos and can have a significant impact on health but also on economy and livelihood. Detailed information on their distribution is lacking and risky food consumption habits exist (e.g. consumption of raw or rare meat/fish). The objectives of this ongoing study are to assess PFBD distribution and risk-related practices in 3 provinces of southern Laos (Savannakhet, Khammuane and Champasak), and establish a cross-sectorial collaboration platform which aims to develop and promote feasible control options addressing needs of affected communities and stakeholders. To facilitate and monitor community involvement and cross-sectoral collaboration among stakeholders integrated approaches such as companion modelling (ComMod) and One-Health are used synergistically. A multidisciplinary research team consisting of vets, public health, environmental, social and participatory modelling scientists has been established and jointly implemented activities using quantitative (e.g. serological sampling) and qualitative methods such as PRA and Participatory Epidemiology. Villagers had lowest PFBD knowledge while para-meds and teachers had highest. Flood or lack of irrigation were ranked highest by villagers while PFBD were never considered as important issues. Serological data on Trichinelloses and Cysticercoses in pigs are currently analysed. Policy engagement and feedback is facilitated through quarterly meetings.